Connections. Doorways: Insprirations, Immigrants, Interactions, and Innovations - Arnold, Virginia A. and Carl B. Smith (New York Macmillan Publishing Company, 1989)
Connections is dedicated to providing learning materials and instructional strategies that will empower teachers and responsibility in the communicative arts. As one important part of a total language arts curriculum, Connections focuses on helping students and teachers make connections for learning vital links that translate current theory into workable teacheing and learning practices.
Keywords: English Practice